1994
DOI: 10.1037/0021-9010.79.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Does the medium matter? The interaction of task type and technology on group performance and member reactions.

Abstract: The authors investigated the hypothesis that as group tasks pose greater requirements for member interdependence, communication media that transmit more social context cues will foster group performance and satisfaction. Seventy-two 3-person groups of undergraduate students worked in either computer-mediated or face-to-face meetings on 3 tasks with increasing levels of interdependence: an idea-generation task, an intellective task, and a judgment task. Results showed few differences between computer-mediated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
274
4
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 465 publications
(297 citation statements)
references
References 61 publications
17
274
4
2
Order By: Relevance
“…These macro trends also are changing the nature of collaborative efforts-at work or anywhere else-by altering the opportunities for collaboration, the need to build collaborations, and the structure of collaborations when they arise. Teams research turned its attention to the impact of digitalization over 20 years ago, with the advent of technologically mediated collaborations (see, for example, Daft & Lengel, 1986;Jarvenpaa & Leidner, 1999;Sproull & Kiesler, 1986;Straus & McGrath, 1994). With the continued march of globalization, more people are collaborating across nationalities, cultures, and languages as well as across space and time.…”
Section: The Changing Ecology Of Teamsmentioning
confidence: 99%
“…These macro trends also are changing the nature of collaborative efforts-at work or anywhere else-by altering the opportunities for collaboration, the need to build collaborations, and the structure of collaborations when they arise. Teams research turned its attention to the impact of digitalization over 20 years ago, with the advent of technologically mediated collaborations (see, for example, Daft & Lengel, 1986;Jarvenpaa & Leidner, 1999;Sproull & Kiesler, 1986;Straus & McGrath, 1994). With the continued march of globalization, more people are collaborating across nationalities, cultures, and languages as well as across space and time.…”
Section: The Changing Ecology Of Teamsmentioning
confidence: 99%
“…Students learning in CSCL environments have been shown to experience lower participation levels (Lipponen et al, 2003), more conflict (Hobman et al, 2002), less group cohesion (Straus, 1997;Straus & McGrath, 1994) and less satisfaction (Baltes, Dickson, Sherman, Bauer, & LaGanke, 2002) than students in contiguous groups. In other words, students working in CSCL environments do not always reach their full potential.…”
Section: Social and Cognitive Benefits Of Groups In Cscl Environmentsmentioning
confidence: 99%
“…Task-Interdependence: Straus and McGrath (1994) and Andres and Zmud (2002) found that highly interdependent tasks required richer information exchanges to clarify task assignments and project requirements, develop effective task performance strategies, make decisions, and obtain performance feedback. These results are in line with Thompson's (1967) suggestion that the higher the level of interdependence, the more difficult and less standardized the suggested form of coordination (see also Daft and Lengel 1984).…”
Section: Proposition 1b: Managerial Tasks Of High Non-routineness Shomentioning
confidence: 99%